The obstacles facing Riyada- financed projects – A field study from the perspective of an entrepreneur in Asir region – - Al- Qahtani, Dalia Mushabab (Journal of Economic, Administrative and Legal Sciences, 2021)
The present research aimed to identify constraints facing projects funded by Riyadah: a field study from Riyadah's perspective in Assir region. And to study the hypotheses of the study represented in the presence of a statistically significant impact of the financing obstacles facing Riyada- financed projects in Aseer region The research was based on the descriptive and analytical approach, and the research population included all owners of the projects funded by Reyadah in Asir region, and a simple random sample consisted of (150) respondents was selected. The study concluded that the funding constraints facing projects funded by Riyadah in Assir region were of a average ratio, that the marketing constraints facing projects funded by Riyadah in Assir region were of high ratio, and that the administrative and organizational constraints facing projects funded by Riyadah in Assir region were of high ratio. Also, it was concluded that there is a statistically significant impact on each of (funding constraints, marketing constraints, and administrative & organizational constraints) facing projects funded by Riyadah in Assir region. The research recommended the necessity for Riyadah Institution to give the owners of the funded projects specialized courses in management and organization that help them in carrying out the tasks assigned to them, and the necessity to follow up the funded projects periodically so that the performance is evaluated on an ongoing basis and the mistakes are corrected. As well, Riyadah Institution has to provide help and assistance for various categories in order to create different job opportunities for many people.
Keywords: obstacles; funded projects; entrepreneurship